The New Economics of Capital Controls Imposed for Prudential Reasons+L4888 - Korinek, Anton (Washington, D.C. : International Monetary Fund, 2011)
This paper provides an introduction to the new economics of prudential capital controls in emerging economies. This literature is based on the notion that there are externalities associated with financial crises because individual market participants do not internalize their contribution to aggregate financial instability when they make their finacing decisions. As a result they impose externalities in the form of greater financial instability on each other, and the private financing decisions of individuals are distorted towards excessive risk-taking. We discuss how prudential capital controls can induce private agents to internalize these externalities and thereby increase macroeconomic stability and enhance welfare.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet